Information about secondary prevention in coronary patients: A comparison between Italian and Brazilian Application of MICRO-Q Questionnaire - Lima De Melo Ghisi G.* (2010)
Background: The MICRO-Q (MaugerI CaRdiac preventiOn Questionnaire) is a self-administered questionnaire addressed to the evaluation of information regarding secondary prevention in patients with coronary heart disease (CHD). The aim of this study was to compare the results from Italian and Brazilian application of MICRO-Q. Methods: the instrument was administered to 500 coronary patients (250 Italian and 250 Brazilian), 117 female and 383 male, aged on average 61.16 years (SD=9.74; range: 33-86), participants of cardiac rehabilitation programs. The Italian MICRO-Q has 26 items, 18 true statements and 8 false, with responses true, false and 'don't know', with three separate scores: correct, uncorrect and uncertain. The Brazilian MICRO-Q has 25 items, 18 true statements and 7 false, with the same responses and scores. To verify and compare results we used Independent-Sample T Test, ANOVA and Bonferroni Post-hoc. Results: The analysis of mean total scores of Italian and Brazilian applications showed statistically significant differences for correct answers (p<0.001) and for 'don't know' answers (p<0.001). 18 statements had significant (p<0.005) differences between applications in the two countries. Conclusion: Despite differences between Italy and Brazil, the analysis of MICRO-Q applications showed a similar mean score percent of correct answers, indicating enough knowledge about secondary prevention of CHD.